Increasing the competitiveness of rail transport in Poland by revitalizing railway stations and sidings - Paweł Lesiak (Przegląd Komunikacyjny)
Abstract: The main subject of the study is to present the negative impact of the degradation and underdevelopment of point infrastructure on the functioning of the freight transport system in Poland. The author proves that the revitalization of railway stations and sidings can contribute to increasing the competitiveness of rail transport, especially in the area of competing with road freight carriers for transport orders as part of dispersed transport, as well as securing the transport system in Poland against the effects of increasing congestion in road transport. Unfortunately, in the Third Republic of Poland, the number of railway sidings has been systematically decreasing, and the problems of transporting goods by rail are exacerbated by the optimization of railway infrastructure in terms of fast passenger trains. The plans for renovation and expansion of the railway network take into account the needs of passenger traffic rather than freight, which is manifested, for example, in the elimination of the so-called train passing loops. Keywords: Rail freight transport; Railway sidings; Railway stations; Transport infrastructure; Railway competitiveness